Memahami Fungsi Manajemen Produksi Siaran Dakwah - Rahmi, Ade Laili; Effendy, Erwan; Nasution, Fadly Ardiansyah (Al-Wasathiyah: Journal of Islamic Studies, 2023)
This research was written with the aim of knowing what the function of broadcast production management is in da'wah. The results of the study show that management comes from the word to manage which means to manage, manage. Production management is all activities to run, organize and manage and utilize all available resources effectively and efficiently so as to produce goods or services at optimum cost to increase the increase in resources. Production management of da'wah broadcasts is an activity of organizing, coordinating, and managing da'wah messages so that the da'wah process can run well. There are 4 broadcast production management functions in da'wah namely planning, organizing, directing and supervising.